Numerical Simulation of Flow and Solidification Behavior of Medium Mn steel in Thin Slab Mold - Tian Runyu, Song Bingjun, Peng Zhongyuan, Qiu Yarong, Kong Lingzhong, Yang Jie (Teshugang)
The flow and solidification characteristics of molten steel in thin slab continuous casting mold of medium Mn steel with section of 1 500 mm×90 mm were studied by numerical simulation. The melting and mixing behavior of reactive mold slag was analyzed. The results showed that in case of casting speed of 5 m/min and immersion depth of 300 mm， the temperature of the medium Mn steel fluctuated greatly around about a quarter of the width surface of the lower layer. Due to the slow heat transfer of the shell， the solidified shell of narrow face at the mold outlet was thin and its thickness was only 7.73 mm. The slag rim formed in the continuous casting process of medium Mn steel was slightly smaller in size and mainly consisted of the initial slag layer. The solid slag film was formed by mixing the initial layer and the reaction layer at different stages. The initial solidification of the shell was easy to be uneven due to the change of the slag ingredient in the upper part of the mold.